2014
DOI: 10.1167/iovs.13-13507
|View full text |Cite
|
Sign up to set email alerts
|

Amblyopic Deficit Beyond the Fovea: Delayed and Variable Single-Trial ERP Response Latencies, but Unaltered Amplitudes

Abstract: Our findings revealed the existence of amblyopic deficits at the perifovea when the stimulated cortical area was matched in size to that of foveal stimulation. These deficits manifested themselves only in the temporal structure of the responses, unlike foveal deficits, which affected both component amplitude and latency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Neural response times are also delayed when viewing with the amblyopic eye. Visual evoked responses to fine gratings or checkerboards typically show both reduced amplitudes and increased latencies of the early components (Lombroso, Duffy, & Robb, 1969 ; Spekreijse, Khoe, & van der Tweel, 1972 ; Sokol & Bloom, 1973 ; Tuttle, 1973 ; Arden, Barnard, & Mushin, 1974 ; Yinon, Jakobovitz, & Auerbach, 1974 ; Levi, 1975 ; Levi & Harwerth, 1978a ; Levi & Harwerth, 1978b ; Sokol & Nadler, 1979 ; Manny & Levi, 1982 ; Bankó, Körtvélyes, Németh, Weiss, & Vidnyánszky, 2013 ; Bankó, Körtvélyes, Németh, & Vidnyánszky, 2014 ). Interestingly, a recent study found that amplitudes were reduced only with foveal stimulation but not with cortically scaled perifoveal stimulation, while responses were delayed and more variable at both the fovea and perifovea (Bankó et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Neural response times are also delayed when viewing with the amblyopic eye. Visual evoked responses to fine gratings or checkerboards typically show both reduced amplitudes and increased latencies of the early components (Lombroso, Duffy, & Robb, 1969 ; Spekreijse, Khoe, & van der Tweel, 1972 ; Sokol & Bloom, 1973 ; Tuttle, 1973 ; Arden, Barnard, & Mushin, 1974 ; Yinon, Jakobovitz, & Auerbach, 1974 ; Levi, 1975 ; Levi & Harwerth, 1978a ; Levi & Harwerth, 1978b ; Sokol & Nadler, 1979 ; Manny & Levi, 1982 ; Bankó, Körtvélyes, Németh, Weiss, & Vidnyánszky, 2013 ; Bankó, Körtvélyes, Németh, & Vidnyánszky, 2014 ). Interestingly, a recent study found that amplitudes were reduced only with foveal stimulation but not with cortically scaled perifoveal stimulation, while responses were delayed and more variable at both the fovea and perifovea (Bankó et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These deficits include enhanced crowding as well as problems with stimulus localization, contour integration, texture and second-order pattern perception, shape discrimination, motion sensitivity, stereopsis, eye movements, and oculomotor coordination. Although typically characterized as a foveal visual disorder, amblyopia-related deficits and their neural markers are present across the visual field, including the perifovea (Bankó, Körtvélyes, Németh, & Vidnyánszky, 2014; Ho et al, 2006; Hou, Kim, Lai, & Verghese, 2016; Katz, Levi, & Bedell, 1984). …”
Section: Introductionmentioning
confidence: 99%
“…For each eye position measurement (i.e., a pair of [x,y] coordinates), geometrical distance from the fixation point was calculated. The median distance was used as a measure of fixation stability in each subject separately for each eye with higher distance values meaning less stable fixation 66 , 67 . In addition, we have also calculated to more standard bivariate contour ellipse area (BCEA), which however suffers from normality assumptions and assumes fixation data is elliptically distributed, as opposed to the assumption free distance calculation 67 .…”
Section: Methodsmentioning
confidence: 99%